Factors of real aspect, empathy, confidence, responsivity, reliability that affect community satisfaction in services in Belawang district office, Barito regency, Kuala - Heni Susanti; Roro Rukmini Widiaswari; Normajatun Normajatun (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to determine